2015
DOI: 10.4137/mbi.s24308
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Presence in Selected Tree Nuts and Dried Fruits

Abstract: Sixty-four tree nut samples (almonds, pecans, pine nuts, and walnuts) and 50 dried fruit samples (apricots, cranberries, papaya, pineapple, and raisins) were purchased from local supermarkets and analyzed for fungal contamination using conventional culture as well as molecular methods. The results of our study showed that the highest yeast and mold (YM) counts (5.34 log10 CFU g−1) were found in walnuts and the lowest in pecans. The most common mold in nuts was Aspergillus niger, relatively low numbers of A. fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 32 publications
3
43
1
1
Order By: Relevance
“…The previous studies evaluating the occurrence of fungi in dried fruits showed that the main contamination of dried raisins, pineapple, apricots, and cranberries was molds such as Aspergillus sp. and Penicillium sp [34]. In contrary, the results of this study indicated that dried goji fruits were contaminated especially by heat-resistant yeast.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…The previous studies evaluating the occurrence of fungi in dried fruits showed that the main contamination of dried raisins, pineapple, apricots, and cranberries was molds such as Aspergillus sp. and Penicillium sp [34]. In contrary, the results of this study indicated that dried goji fruits were contaminated especially by heat-resistant yeast.…”
Section: Discussioncontrasting
confidence: 85%
“…The potential microbial spoilage during storage and the potential health hazard due to fungal presence and mycotoxins accumulation is one of the most important concerns regarding to dried fruits [31,32]. It has been shown that dried fruits can be contaminated by fungi and their mycotoxins [33,34], and therefore, monitoring is critical for such fruit quality. However, the phenotype microarray method has not previously been described as a tool for the fast detection of mycological contamination, especially for heat-resistant fungi in dried fruits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indijoje ištyrus 50 graikinių riešutų branduolių, visuose mėginiuose buvo aptikta pelėsinių grybų, kurių koncentracija svyravo nuo 3 iki 5 log 10 ksv/g (Riyaz-Ul-Hassan et al, 2003). JAV visuose 20 tirtų mėginių rasta 2-6 log 10 ksv/g mikromicetų kolonijų (Tournas et al, 2015). Irane taip pat visi graikinių riešutų mėginiai buvo už-teršti pelėsiniais grybais, tačiau ne tokiu dideliu kiekiu kaip kitose šalyse.…”
Section: Tyrimų Rezultatai Ir Jų Aptarimasunclassified